The Road Traveled : Dubai's Journey towards Improving Private Education - A World Bank Review - Thacker, Simon; Cuadra, Ernesto (2016)
As Dubai has grown over the last two decades, the demand for private education has grown with it, a reflection of the number of expatriates settling in the city. Today, 88 percent of all students attend private schools. The surge in demand over this period had in fact been so significant that authorities, recognizing the need to establish a specific governmental entity to oversee the sector s expansion, moved to create the Knowledge and Human Development Authority (KHDA) in 2007. Given the city-state s unique context (in which a majority of the population are expatriates, not Emiratis), the immediate challenge for this new public institution was to identify an appropriate approach for regulating a private education sector. The main objective of the present review is to understand what has motivated KHDA s policy initiatives, what principles have guided design, how they were operationalized, and how they function in real life situations today. In what follows, we look first at the broader context of the issue by giving a brief overview of: (i) the growth of private sector education; and (ii) the rise of public governance reform initiatives in the global education policy agenda. The authors then turn to the case of Dubai: the authors present the argument in the road not traveled before reviewing how that policy framework was translated into its present institutional configuration in Dubai through the development of the institutions that came into being. The authors then reflect on the policy framework in operation, showing how the constituent components function together. The authors end by suggesting some options on potential ways forward that will further enhance the system.